PENGARUH PERSEPSI KUALITAS PELAYANAN, CITRA PERUSAHAAN DAN PERSEPSI KONSUMEN TERHADAP LOYALITAS KONSUMEN BENGKEL SEPEDA MOTOR HONDA AHASS: 0295 PATRA JAYA KOTA BENGKULU - Markoni Markoni (Creative Research Management Journal, 2021)
This study aims to determine the effect of service quality perception, corporate image and consumer perception on consumer loyalty of Honda Ahass Motorcycle: 0295 Patra Jaya Bengkulu City, with a total sample of 50 people, taken by accidental sampling technique data analysis used partial correlation method, simultaneous correlation and multiple regression methods, and the research hypothesis wastested with statistics. The results of the partial correlation analysis show that the three variables of service quality perception, company image and consumer perception will each have a strong, unidirectional and significant effect on consumer loyalty. Meanwhile, simultaneously shows that the three variables together have a very strong and positive and significant effect on consumer loyalty. Thus, every change in the perceived service quality variable, corporate image and consumer perception, either alone or jointly, will be followed by changes in the consumer loyalty variable in the same direction, either increasing or decreasing. The results of Multiple Regression Consumer Analysis show that the balance of the nature and magnitude of the influence of three variables, namely the perception of quality on the Loyalty of Honda Ahass Motorcycles: 0295 Patra Jaya Bengkulu City. with the order of magnitude of influence on the variable of consumer loyalty, each variable is corporate image, then followed by the variable of consumer perception, and perception of service quality.